UAVs and social science: A transformative perspective - Ricky Anak Kemarau; Wan Shafrina Wan Mohd Jaafar; Zaini Sakawi; Nurul Asyiqin Abu Bakar; Aisyah Marliza Muhmad Kamarulzaman; Stanley Anak Suab; Oliver Valentine Eboy; Siti Norliyana Harun; Zulfaqar Sa’adi (Southwestern Social Science Association, 2025)
This study highlights the transformative impact of unmanned aerial vehicles (UAVs) in social sciences, revealing their growing importance across methodologies and ethical considerations. Initially prominent in military use, UAVs now significantly benefit civilian and academic domains, including anthropology, geography, and archaeology. A comprehensive literature review assesses UAV integration into these fields, emphasizing innovative applications and case studies that demonstrate their value in enhancing data collection and research capabilities. UAVs’ ability to gather detailed, wide-ranging geographical information efficiently underscores their methodological revolution in social science research. This paper underscores UAVs’ potential for deeper analysis and the ethical challenges they pose, forecasting their profound effect on future research trends by marrying technological advances with ethical mindfulness. In moving forward, this study advocates for interdisciplinary collaborations and the development of robust ethical frameworks to maximize the benefits of UAVs while mitigating potential risks, paving the way for their responsible and impactful application in social science research.